Relasi Pembangunan Berbasis Gender Dalam Peningkatan Kompetensi Pengetahuan Dalam Reproduksi Perempuan Di Tapanuli Selatan - Elfyda Rahmadani (Ittishol: Jurnal Komunikasi dan Dakwah, 2024)
This study explores and analyzes gender-based development relations in improving knowledge competence in women's reproduction in South Tapanuli. The main focus of this study is to identify the impact of gender-oriented development programs on women's reproductive knowledge and skills in the region. This research method uses qualitative data collection techniques through in-depth interviews, participatory observation, and document analysis. The respondents to the study involved women from various walks of life in South Tapanuli who had participated in gender-based development programs. The results of the study show that gender-based development relations have a positive impact on improving women's reproductive knowledge competencies in South Tapanuli. Programs focusing on gender aspects can provide better access to reproductive health information and services. In addition, women's participation in decision-making related to their health is increasing, significantly contributing to increased reproductive knowledge and awareness. However, the study also highlights some of the challenges and obstacles still faced, such as unequal access to gender-based development programs, persistent gender stereotypes, and the need for further integration in developing and implementing development programs. This research is expected to contribute to further understanding of the effectiveness of gender-based development relations in improving women's reproductive knowledge competence. The implications of this research can be the basis for related parties in designing and implementing more inclusive and sustainable development programs.